Diagnosis and management of acute coronary syndrome in an outpatient setting: good guideline adherence in Swiss primary care. Issue 5 (8th May 2012) - Tandjung, Ryan; Senn, Oliver; Rosemann, Thomas; Loy, Monika
Abstract Background Switzerland lacks of national guidelines for the initial treatment of an acute coronary syndrome (ACS). ACS is not as frequent in an outpatient setting as in an emergency department; nevertheless, missing an ACS is associated with high morbidity and mortality. We wanted to observe actual infrastructure and performance based on case vignettes in outpatient general practitioners (GPs) and cardiologists (CAs); as a second outcome, we wanted to compare GPs to CAs. Methods We conducted a postal vignette‐based survey to investigate the management of outpatients presenting with acute chest pain by doctors in private practice. The use of troponin and cardiac stress testing for the evaluation of acute chest pain as well as referral practice and use of antiplatelet agents were assessed and compared between GPs and CAs. Results There were 507 of the 571 respondents (response rate 39.7%) who were CAs (36) or GPs (471) and were included in the analysis. Whereas all CAs were equipped with electrocardiogram (ECG), cardiac stress testing and troponin assays, the majority of GPs had an ECG (97.8%) and applied troponin testing (76.3%), and 38.7% performed cardiac stress testing. The vast majority responded to directly refer a STEMI to the next catheter lab (87.7%), or in the case of a troponin‐positive NSTEMI, to an inpatient ward (94.1%) with no difference between GPs and CAs. A majority of the GPs responded to use antiplatelet agents in the case of a STEMI (89.6%) and reported further workup with cardiac stress testing in the case of a troponin‐negative acute chest pain (78.7%), which was lower compared to CAs who applied antiplatelet agents and cardiac stress testing in 100% and 97.0%. Conclusions We could show that international guideline adherence in ACS of GPs is high and GPs perform as well as CAs. Nevertheless there is room for optimization in the antiplatelet therapy and the use of cardiac stress testing in a low‐risk population. National guidelines for treatment of an ACS in an outpatient setting are indicated.